The federal judiciary strengths and weaknesses - Posner, Richard A (Harvard University Press, 2017)
"No sitting federal judge has ever written so trenchant a critique of the federal judiciary as Richard A. Posner does in this, his most confrontational book. He exposes the failures of the institution designed by the founders to check congressional and presidential power and resist its abuse, and offers practical prescriptions for reform"--